Is herpes zoster vaccine safe and effective for preventing zoster and postherpetic neuralgia?. Issue 9 (September 2015) - Colson, Emily; TenHarmsel, Aaron; Geurin, Michael D.
Abstract : Evidence‐Based Answer : The herpes zoster vaccine is effective in preventing herpes zoster (SOR: B, large RCT). The zoster vaccine does not further reduce the incidence of postherpetic neuralgia (PHN) beyond simply reducing the incidence of herpes zoster (SOR: B, large RCT). The vaccine does cause localized reactions in about half of patients (regardless of a history of prior herpes zoster), but serious adverse events are rare (SOR: A, systematic review).